Radical Polymerization Kinetics of Hexyl Methacrylate in Dimethylsulfoxide Solution - Hala Rahman Noormohamad; Ameen Hadi Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this study, we conducted a series of polymerization studies of hexyl methacrylate in dimethyl sulfoxide with (0.1 - 0.4) mol dm-3 of monomer and (1 10-3 – 4 10-3) mol dm-3 of benzoyl peroxide as initiators at 70 °C. Using the well-known conversion vs. time technique, the effects of initiator and monomer concentration on the rate of polymerization (Rp) were studied. An initiator of order 0.35 was obtained in accordance with theory and a divergence from normal kinetics was detected with an order of 1.53 with respect to monomer concentration. The activation energy was determined to be (72.90) kJ mol-1, which does not correspond to the value of most thermally initiated monomers. The observed value of activation energy suggests that propagation and termination reactions have equal activation energy and the difference between them is nearly zero. The average degree of polymerization (DPn) decreased as benzoyl peroxide concentration increase whereas an increase in solvent polarity has slightly increased rate of polymerization value.